Pickup Hub Location Problem with Prospective Customers in Rural Area: A Case Study - Zhou, Yanjie; Luo, Liping; Wang, Yongsheng; Feng, Xuehao; Huang, Zhihong; Feng, Weihua; Pang, Lei (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This paper addresses the pickup hub location problem in rural areas, considering dynamic changes in prospective customers and optimizing equity. The problem involves selecting optimal pickup hub locations from candidate hubs while minimizing transportation costs, measured as the distance between a set of determined customers and pickup hubs. A nonlinear fractional integer programming model is developed to formulate the problem. A scenario-based Dinkelbach’s algorithm combined with a mathematical reformulation approach is proposed to solve the problem efficiently. The effectiveness of the proposed method is demonstrated through a case study on the location selection of smart cigarette delivery lockers. The results highlight the method’s ability to balance equity, offering a practical solution for logistics planning in rural areas. The key contributions of this study are: (1) a novel pickup hub location model that accounts for dynamic customer changes and (2) validation of the approach through a real-world case study, showcasing its applicability and effectiveness.